Complex pathologic differential diagnosis of precancerous processes and gastric cancer - Markovskiy, V.D.; Kharchenko, A.V. (Pathologia, 2013)
For the first time, a special comprehensive study of the phenotypes of dysplasia of gastric mucosa by histological techniques and their respective genomes using molecular-biological method of ISSR-PCR was performed. Main effect of precancerous lesions, chronic atrophic gastritis and Helicobacter pylori infection in the formation of precancerous changes in the form of gastric epithelium dysplasia and in the form of intestinal metaplasia foci was shown. We study manifestations of the mitotic regime in various zones of gastric mucosa in patients with chronic duodenal ulcer, gastric ulcer, and ulcero-infiltrative gastric cancer. The regularities and characteristics of the frequency and prevalence of precancerous processes in different zones of stomach in patients with duodenal ulcer and stomach ulcer were determined. Diagnostic criteria for differenting them from stomach cancer were worked out. On the material of postoperative stomach gastrobiopsies repeated during five years, statement about heterogeneity of gastric mucosa epithelium dysplasia of the second and third degree was grounded, and criteria for the detection of early gastric cancer using histological methods in combination with the method of ISSR-PCR were found. The use of ISSR-PCR method for detecting tumor cells in peripheral blood of patients with category М0 cancer revealed their presence in 27,8% cases, which indicates risk of early metastasis in these patients.